ANALISIS IMPLEMENTASI KEBIJAKAN BUKU SEKOLAH ELEKTRONIK (BSE) KEMENTERIAN PENDIDIKAN NASIONALDI SEKOLAH MENENGAH ATAS (SMA) KOTA YOGYAKARTA (Studi kasus di SMA Negeri 8 dan SMA Negeri 9 Yogyakarta) - Zaenal Irawan, Maya Eka Sari, Muthia Umi Setyoningrum (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
With the rapid development of information and communication technologies leads the Ministry ofNational Education to conduct a basic reformation on educational books with by issuing innovationpolicies in the form of School Book Electronic (BSE) in order to provide a mass of textbooks, with low‐cost,good quality and technology. This study was aimed at finding out how the BSE policy was implementedand what obstacles were found in the field.The study listed different types of research with a descriptive qualitative approach, using in‐depthinterviews, observation, and triangulation documentation as data collection techniques. The sources ofdata in this study are the Head of Department of Education, headmasters, teachers, school staff,students and parents who were selected by using a purposive sampling technique and snowball samplingand the results of observation.The research showed SMA Negeri 8 Yogyakarta SMA and SMA Negeri 9 Yogyakarta were ready withthe necessary infrastructures to implement the BSE policy. However, the implementation of BSE policy atboth schools were not effective. This was due to the following reasons: (1) Insufficient socialization bythe government, (2) Human resources that have not been able to use particular technologies related toInternet, (3) unavailability of the management system in the use of BSE; (4) The limited collections oftextbooks that are available in BSE and the inaccessibility of BSE ; (5) Status / Quality of schools. SMANegeri 8 Yogyakarta as standard international schools and SMA Negeri 9 Yogyakarta as a nationalstandard school think that the materials in BSE only includes basic competencies (standards). So, BSE isnot suitable to support the achievement of school targets, and (6) Lack of strong legal base for BSE.There is no clarity of shared the authority, tasks and roles that must be executed by each institutionincluded in the hierarchy of National Education Ministry.Keywords: Policy Implementation, BSE